Interview “Disasters, environmental changes and migration in historical perspective” - Queiroz, Ana Isabel (2020)
Uwe Lübken is professor of American History at the Ludwig- -Maximilians-University, in Munich. He has held teaching and research positions at the universities of Cologne, Munich, Münster, and the German Historical Institute in Washington, dc. He has published several monographs, edited volumes, special issues, and articles on (American) Transnational History and the “History of Natural Hazards and Catastrophes”. His current work explores the intersections of mobilities and the environment. In May 2019 Uwe Lübken was in Lisbon for a cycle of workshops and conferences about the “History of Poverty and Hunger”, organized by the Institute of Contemporary History (ihc, nova, fcsh).1 This conversation took place one day after he delivered his talk. We first met him downtown and walked in the direction of the river Tejo. While we walked and visited some landmarks related to disasters (e. g., Igreja de São Domingos, Chiado, Convento do Carmo’s ruins), we evoked the great earthquake of 1755 and talked about flammable cities, disaster memory, and city-river relationships in historical perspective. We finished our trip on the south bank of the river, in Cacilhas (Almada), where we conducted this interview, having Lisbon in the background.